Childhood maltreatment and clinical severity of treatment‐resistant depression in a French cohort of outpatients (FACE‐DR): One‐year follow‐up. Issue 4 (30th January 2020) - Yrondi, Antoine; Aouizerate, Bruno; Bennabi, Djamila; Richieri, Raphaëlle; D'Amato, Thierry; Bellivier, Frank; Bougerol, Thierry; Horn, Mathilde; Camus, Vincent; Courtet, Philippe; Doumy, Olivier; Genty, Jean B.; et al.
Abstract: Background: Childhood maltreatment is associated with major depressive disorder (MDD). It not only increases the risk of lifetime MDD, but it also aggravates its course. Among depressed patients, 20–30% of them experience treatment‐resistance depression (TRD). We aimed to assess the association between childhood maltreatment, severity of depression in a unipolar TRD sample, and patient outcomes after one‐year of follow‐up. Methods: Patients were recruited for a prospective cohort from the French network of TRD expert centers. Depressive symptom severity was assessed with the Montgomery–Åsberg Depression Rating Scale (MADRS) and the Quick Inventory of Depressive Symptomatology self‐report (QIDS‐SR). Childhood maltreatment was evaluated with the Childhood Trauma Questionnaire (CTQ). Results: In total, 256 patients filled in the CTQ at baseline between 2012 and 2019. At baseline, the MADRS score was associated with CTQ score ( β  = .185; p  = .004). QIDS was also associated with CTQ scores ( β  = .27; p  < .001). Regarding the different subtypes of childhood maltreatment, MADRS was associated with physical ( β  = .21; p  = .005) and sexual abuse ( β  = .22; p  = .002), while QIDS with physical abuse ( β  = .304; p  < .001) and physical neglect ( β  = .254; p  < .001). However, we did not find any significant association focusing on the other types of traumas. During a 1‐year follow‐up focusing on remission, CTQ scores (baseline) were less important in remittent patients [n = 38; CTQ score = 39.26 (9.68)] than in nonremittent ones [n = 92; CTQ score = 46.02 (17.53)] ( p  = .027). There was no significant difference among remitters and nonremitters based on trauma subtypes. At baseline, CTQ scores had a significant influence on remission at 1 year ( χ 2 (1) = 5.57; p  < .05). We lost this influence adding MADRS scores at baseline in the model ( p  = .063). Conclusion: We highlighted a significant association between the severity of depressive disorders and childhood maltreatment in the TRD population. Information about a history of childhood maltreatment helps in identifying individuals who could be less likely to go into remission after treatment.